Understanding the Meaning of Self-Identity Construction of Salatiga Community - Darmastuti, Rini; Edi, Sri Winarso Martyas; Christianto, Erwien; Prabawa, Titi Susilowati (Universitas Semarang, 2019)
The Salatiga community is unique than other communities. It lies in the identity they have. Salatiga community had always interacted with the migrants, since the Dutch colonial era. Logically, interactions with migrants will influence the identity of the Salatiga community. In fact, the identity of the Salatiga community still present to this day. Interaction with migrants actually create tolerance. Using a constructivist approach, this paper attempts to construct the identity of Salatiga community. This article using qualitative method with an ethnographic approach to communication. Based on the analysis conducted, as the first place, the construction of Salatiga community identity is the manifestation of Raden Mas Said s doctrine which emphasizes on togetherness, and accepting others. Secondly, the doctrine of Raden Mas Said become a basic for the emergence of multiculturalism understanding in the lives of the Salatiga community. Thirdly, the identity of the Salatiga community is a symbol of tolerance.